Educação inclusiva e a participação das famílias na educação infantil: breve levantamento de produções acadêmicas - 2017 a 2022 - Santos, Louise de Freitas (Universidade Federal de São Carlos, 2023)
This research aims to understand what are the approaches analyzed in research related to inclusive education in early childhood education and the participation of families. To conduct this work, a bibliographical research was used with the BDTD theses and dissertations bank in order to map and understand the main subjects studied in relation to the content and which approaches were used by research carried out in the period from 2017 to 2022. It begins with the exposition of the concepts, carried out through research in legal documents, of early childhood education and inclusive education, and follows the methodological track used and from the results obtained makes a discussion on the topic.
Inclusive education and the participation of families in early childhood education: brief survey of academic productions - 2017-2022
Keywords: Educação Infantil; Educação Inclusiva; Participação das Famílias; Early Childhood Education; Inclusive Education; Participation of Families; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO